Non-elective removal of peripherally inserted central catheter: preventive measures and management of causes in pediatrics and neonatology (Research, Society and Development, 2023)
Objective: to synthesize the scientific production related to the prevention of non-elective removal of the Peripherally Inserted Central Catheter and the management of its complications. Method: this is a narrative review of the literature with searches performed in the years 2014 to 2019, using four electronic databases. In the initial selection, 241 studies were found among articles, dissertations and theses, which after applying the inclusion and exclusion criteria were restricted to 20 studies that were considered for research purposes. Results: among the recommendations brought by the studies, the following stand out: prevention of infection with hand washing when handling the device, disinfection with alcohol to 70% of connections when accessing them, aseptic insertion and dressing change, paying greater attention to measurement of the catheter to be introduced, stabilization of the catheter with safe and adequate fixation, maintenance of the dressing clean and dry, routine of washing the catheter with pulsating flush and positive pressure and periodic evaluation of the insertion site. Conclusion: the authors of the analyzed studies emphasized qualification and training as a primordial and essential strategy for the improvement of skills and the successful maintenance of this device. Finally, the study contributes to the improvement of doing and nursing as a science.